Pengaruh Metode Team Quiz Terhadap Hasil Belajar Pendidikan Agama Islam Siswa Kelas X - Putri, Rahmadani; Rahman, Rini (An-Nuha, 2025)
This research is motivated by the low learning outcomes of students in the learning process and teachers have not applied varied learning methods. This study aims to (1) find out the description of student value data before the application of the team quiz method, (2) find out the description of student value data after the application of the team quiz method, (3) find out the effect of the team quiz method on the learning outcomes of Islamic Religious Education of Class X Students. This type of research is quantitative research with a Quasi Experimental Design research design, with a Non Equivalent Control Group Design form. Data analysis techniques using the t-test to test the hypothesis, namely the Paired Sample T-Test and Independent Sample T-Test with the help of the SPSS version 16 application. The findings of the study were (1) the average pre-test value for the experimental group was 68.81 and the average pre-test value for the control group was 65.96 (2) the average post-test value for the experimental group was 91.33 and for the control group was 80.15. (3) There is an effect of the application of the team quiz learning method on the learning outcomes of Islamic Religious Education of Class X Students which can be seen from the results of the hypothesis test calculation using the t-test obtained in the experimental class which obtained a value of t count = 8.101 and t table = 2.056 So t count > t table and sig. (2-tailed) <0.05 Ho is rejected and Ha is accepted.